Politics of Protest in Pakistan: An Analysis of Political Implications of Pakistan Tehreek E Insaf’s Dharna in Islamabad (2014) - Ullah, Yaseen; Raza, Aamir; Gul, Saba (The Lighthouse Journal of Social Sciences, 2022)
Demonstrations, agitations, and protests are part of the democratic political process. Protests play a significant role in shaping the polity of a country, as they can challenge existing power structures and bring attention to social, political, and economic issues that may have been previously ignored or marginalized. Protest politics have played a crucial role in the history of Pakistan. These demonstrations were organized for a variety of causes; some were against civilian governments, others against martial laws, and yet others for the restoration of democracy and the judiciary. This present study discusses the recent protest and its political implications. The 126-day protest in Islamabad over the alleged rigging of the 2013 elections, led by Imran Khan's Pakistan Tehreek e Insaaf (PTI) was popularly known as "Dharna." Most of the data is based on interviews with students, lawyers, and political activists in Nowshera, Peshawar, and Lahore, Pakistan. We argue that this Dharna has created awareness among the people, helped PTI win the elections of 2018, set a precedent for political as well as non-political forces to stage protests and put the government under pressure, encouraged the culture of civil disobedience, weakened the revived process of democracy, and reinforced the non-democratic forces in the country. For this reason, the prolonged dharna has far-reaching consequences for Pakistan's politics.